Aliran al-Hikmah Muta'aliyah: Kajian Komprehensif Teosofi Transenden Mulla Sadra - Hadi, Rahmad Tri (JURNAL AL-AQIDAH, 2024)
This paper aims to explore the main characteristics of al-Hikmah Muta'aliyah and examine how this philosophy harmonizes philosophical and theological views in Islam. In addition, this article analyzes the relevance of Mulla Sadra's philosophy in the context of contemporary Islamic thought. The method used in this research is a descriptive-analytical method with a comprehensive approach. The primary data used in this research are the works of Mulla Sadra. The secondary data in this study are books, journal articles, and other websites that discuss Mulla Sadra's thoughts. The results of this study indicate that al-Hikmah Muta'aliyah or Transcendent Theosophy developed by Mulla Sadra in the 17th century is one of the most influential philosophical thought systems in Islamic philosophy. By combining elements from philosophy, theology, and mysticism, Mulla Sadra created an innovative framework that integrates existential, ontological, and epistemological aspects. The main tenets in al-Hikmah Muta'aliyah include asālat al-wujūd (primacy of existence) that places existence as the fundamental reality compared to essence, as well as tashkīk al-wujūd (gradation of existence) that supports the unity of existence by considering the diversity of manifestations. Other concepts, such as harakah al-jawhariyyah (substantial movement) and ilm al-hudhūrī (knowledge through presence), provide new views in understanding the soul's development and existence. Their relevance in the context of contemporary Islamic thought lies in their ability to combine rational, spiritual, and transcendental aspects in understanding reality and provide a broader perspective in addressing the intellectual and moral challenges of the modern world.